Pengaruh Lingkungan Kerja, Beban Kerja, Stres Kerja Terhadap Kepuasan Kerja Aparatur Desa Di Desa Karangbayat Kecamatan Sumberbaru Kabupaten Jember - Nurlailiyah, Nurlailiyah; Suharto, Akhmad; Ika Sari, Maheni (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
This study aims to analyze the influence of work environment, workload, and work stress on job satisfaction of village officials in Karangbayat Village, Sumberbaru Subdistrict, Jember Regency. This research develops theories related to the relationship between work environment, workload, work stress, and job satisfaction, especially in the context of village government which is still rarely researched academically. This type of research is explanatory research that aims to explain the causal relationship between the variables studied and test the hypotheses that have been formulated. The analysis method used in this research is multiple linear regression analysis. The results of hypothesis testing show that partially each independent variable has a significant effect on job satisfaction. Work environment has a positive and significant effect on job satisfaction with a t-count value of 3.165 which is greater than the t-table of 1.979 and a significance value of 0.000 <0.05. This shows that the better the work environment, the higher the level of job satisfaction of the village apparatus. Workload also has a significant effect on job satisfaction with a t-count value of 5.676> t-table 1.979 and a significance of 0.000 <0.05. A balanced workload can increase job satisfaction, while excessive workload can reduce job satisfaction. Furthermore, job stress is proven to have a negative and significant influence on job satisfaction with a t-count value of 2.968 > t-table 1.979 and a significance of 0.001 <0.05, which means that the higher the job stress, the lower the level of job satisfaction of the village apparatus.